Application of Integrated Emergency Care Model Based on Failure Modes and Effects Analysis in Patients With Ischemic Stroke - Yang, Yuying; Chang, Qing; Chen, Jing; Zou, Xiangkun; Xue, Qian; Song, Aixia (Frontiers in Surgery, 2022)
Purpose To explore the application value of an integrated emergency care model based on failure modes and effects analysis (FMEA) in patients with acute ischemic stroke (AIS). Methods According to the convenience sampling method, 100 patients with AIS who visited the emergency department in our hospital from October 2018 to March 2019 were randomly selected as the control group and received routine emergency care mode intervention. Another 100 AIS patients who visited the emergency department from April to October 2019 were selected as the intervention group and received the integrated emergency care model based on FMEA. The total time spent from admission to completion of each emergency procedure [total time spent from admission to emergency physician reception (T0−1), total time spent from admission to stroke team reception (T0−2), total time spent from admission to imaging report out (T0−3), total time spent from admission to laboratory report out (T0−4), and total time spent from admission to intravenous thrombolysis (T0−5)] was recorded for both groups. The clinical outcome indicators (vascular recanalization rate, symptomatic intracerebral hemorrhage incidence, mortality rate) were observed for both groups. The National Institutes of Health Stroke Scale (NIHSS) score and Barthel score were evaluated for both groups after the intervention. The treatment satisfaction rate of the patients was investigated for both groups. Results The total time of T0−1, T0−2, T0−3, T0−4, T0−5 in the intervention group (0.55 ± 0.15, 1.23 ± 0.30, 21.24 ± 3.01, 33.30 ± 5.28, 44.19 ± 7.02) min was shorter than that of the control group (1.22 ± 0.28, 4.01 ± 1.06, 34.12 ± 4.44, 72.48 ± 8.27, 80.31 ± 9.22) min (P < 0.05). The vascular recanalization rate in the intervention group (23.00%) was higher than that in the control group (12.00%) (P < 0.05). There was no statistical significance in the symptomatic intracerebral hemorrhage incidence and mortality rate in the two groups (P > 0.05). After intervention, the NIHSS score of the intervention group (2.95 ± 0.91) was lower than that of the control group (6.10 ± 2.02), and the Barthel score (77.58 ± 7.33) was higher than that of the control group (53.34 ± 5.12) (P < 0.05). The treatment satisfaction rate in the intervention group (95.00%) was higher than that of the control group (86.00%) (P < 0.05). Conclusion Through FMEA, the failure mode that affects the emergency time of AIS patients is effectively analyzed and the targeted optimization process is proposed, which are important to enhance the efficiency and success rate of resuscitation of medical and nursing staff and improve the prognosis and life ability of patients.